THE CONTRIBUTION OF GOVERNMENT AND NON GOVERNMENTAL ORGANIZATION SUPPORT FOR EDUCATION IN BENIN CITY, NIGERIA. - FA, Ehiaghe (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
This study was aimed at identifying and examining the various supports for secondary school education by the government and NGOs in Benin City. Out of the fifteen (15) experiencing government refurbishment in Edo State, 4 are in Benin metropolis and all 4 were sampled. 40 questionnaires were administered (10 for each school). The results of the investigation carried out using percentage distribution and Chi Square Testing. The contributions of both Government and NGO were responsible for the positive improvement in the educational system in Benin City and in Nigeria since independence, although NGO support have not really been significant. The Planning, Research and Statistic Department of Post Primary Education Board and that of the Ministry of Education in the state should carry out the actual counting of schools and their staffs as well as students in the school so that they can be suitably used for planning.